The Impact of Technological Change on Corporate Management: A Literature Review Analysis - Ibrahim KAHYA; Torsten HUSCHBECK; Zuzana SKORKOVA (Communications of International Proceedings, 2024)
This study systematically reviews the literature on the impact of technological change on corporate management, aiming to fill the gap in understanding how digital transformation influences managerial practices and decision-making. The motive behind this study is to explore the intersection of technological advancements, risk management, and decision-making in corporate settings. The literature reveals a void in comprehensive analyses on how technologies such as artificial intelligence (AI) and data analytics shape enterprise risk management (ERM) and decision-making processes. Methodologically, this study employs a systematic literature review (SLR) approach, analyzing 25 academic articles selected from the Web of Science database. The articles were chosen based on their relevance to risk management, decision-making, and technological advancements, with a focus on publications from 2021 to 2024. The findings underscore the transformative potential of AI and data analytics in enhancing ERM, improving supply chain transparency, and fostering innovation. Additionally, the study highlights the importance of addressing cognitive biases and organizational culture in decision-making processes. Practical recommendations include leveraging advanced technologies for better risk management and decision-making, enhancing transparency and trust among stakeholders, and optimizing HR tasks while considering ethical and legal issues. Future research should delve into advanced analytical techniques, the influence of cultural factors on supply chain performance, and AI integration in HR management to further enhance organizational performance and innovation. This review emphasizes the necessity of understanding technological impacts, behavioral influences, and systemic approaches to advance both theoretical and practical aspects of corporate management.
Keywords: Risk Management; Decision Making; Artificial Intelligence; Behavioural economics; Cultural influences; Bias